2021
DOI: 10.3390/ijms222212548
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genome Analysis of Genes Regulating Compound Inflorescences in Tomato

Abstract: Inflorescences are the main factor affecting fruit yield. The quantity and quality of inflorescences are closely related to fruit quality and yield. The presence of compound inflorescences in cherry tomatoes is well established, and it has been discovered by chance that compound racemes also exist in tomatoes. To explore the formation of compound inflorescences in tomato, transcriptome sequencing was performed on Moneymaker (MM) and Compound Inflorescence (CI) plants. In-florescences were collected in three pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…Also, significantly improved stability over repeated water splitting reactions was achieved compared to pristine Cu 2 O. The distinct photocatalytic difference of facetdependent Cu 2 O was also studied by Huang et al 80 The electron paramagnetic resonance (EPR) measurements indicated a higher production of hydroxyl radicals for the photo-irradiated Cu 2 O rhombic dodecahedra than for the octahedra, but no radicals were produced from photoirradiated Cu 2 O cubes. The Cu 2 O {100} face may present a high energy barrier through its large band edge bending or electrostatic repulsion, preventing charge carriers from reaching this surface.…”
Section: Advantages Of Facet and Phase Engineering For Water Splittingmentioning
confidence: 91%
“…Also, significantly improved stability over repeated water splitting reactions was achieved compared to pristine Cu 2 O. The distinct photocatalytic difference of facetdependent Cu 2 O was also studied by Huang et al 80 The electron paramagnetic resonance (EPR) measurements indicated a higher production of hydroxyl radicals for the photo-irradiated Cu 2 O rhombic dodecahedra than for the octahedra, but no radicals were produced from photoirradiated Cu 2 O cubes. The Cu 2 O {100} face may present a high energy barrier through its large band edge bending or electrostatic repulsion, preventing charge carriers from reaching this surface.…”
Section: Advantages Of Facet and Phase Engineering For Water Splittingmentioning
confidence: 91%
“…Previously, strong EPR signals have been recorded for Cu 2 O octahedra. 22 In recording these EPR spectra, the amount of radicals is not precisely known. The DMPO concentration can decrease, as many substances in the air can react with DMPO and produce radicals.…”
Section: Photocatalysis Resultsmentioning
confidence: 99%
“…To enhance the photocatalytic activity, surface decoration with metal particles and graphene sheets, graphitic carbon nitride, and the formation of semiconductor heterostructures, have generally been employed. 3,[22][23][24][25][26][27][28] Interestingly, Cu 2 O cubes have remained inactive even after forming heterostructures with ZnO, ZnS, CdS and Ag 3 PO 4 particles, and suppressed activity can sometimes be observed for octahedra and rhombic dodecahedra, demonstrating that the conventional band energy alignment analysis without consideration of the effect of the contacting planes to interfacial band bending cannot correctly explain the photocatalysis outcome. 3 The next untapped strategy to increasing photocatalytic activity should be surface molecular functionalization.…”
Section: Introductionmentioning
confidence: 99%
“…fa mutants convert many flowers in secondary buds and produce highly branched inflorescences [ 62 , 63 ]. These mutants are unable to develop complete flowers and have a late flowering phenotype, increasing the number of leaves below the first and successive inflorescences [ 64 ]. Moreover, LeHsp100 also interact with other three Hsps (SlHsp40-105, SlHsp70-20 and SlHsp70-24) exhibiting missense variants in the gene coding sequence.…”
Section: Discussionmentioning
confidence: 99%